2008
DOI: 10.1530/rep-08-0135
|View full text |Cite
|
Sign up to set email alerts
|

The seminal coagulum favours passage of fast-moving sperm into the uterus in the black-handed spider monkey

Abstract: In addition to gametes, mammalian internal fertilisation has required the evolution of assorted anatomical, physiological and biochemical devices to deal with intra-and inter-sexual conflict such as sperm competition and female cryptic choice respectively. The seminal coagulum of primates and other mammals is viewed as one of such devices. Among primates, the seminal coagulum characteristically occurs in multi-male and multi-female species, leading us to suppose that it intervenes in sperm competition. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The observed semen pH (7.7) was similar to that reported in other Neotropical primate species, in semen from C goeldii (7.61) and C jacchus (7.6), and lower than that described in A caraya (8.9 and 8.1) and A geoffroyi (8.0) . Semen pH is dictated by the balance between accessory glands secretions’ pH, mostly alkaline secretions from seminal vesicles and acidic secretions from prostate .…”
Section: Discussionsupporting
confidence: 81%
“…The observed semen pH (7.7) was similar to that reported in other Neotropical primate species, in semen from C goeldii (7.61) and C jacchus (7.6), and lower than that described in A caraya (8.9 and 8.1) and A geoffroyi (8.0) . Semen pH is dictated by the balance between accessory glands secretions’ pH, mostly alkaline secretions from seminal vesicles and acidic secretions from prostate .…”
Section: Discussionsupporting
confidence: 81%
“…Some caution is advisable, however, as it transpires that human vaginal pH is exceptionally low, averaging 4.5, as compared to pH values of 7.6 (Macaca nemestrina), 5.0-5.6 (Papio anubis), 5.5 (P. cynocephalus) and 6.5 (A. geoffroyi) at around the time of the oestrogen peak [Miller et al, 2016]. Nonetheless, in the last of the species listed (the black-handed spider monkey, A. geoffroyi), Hernández-López et al [2008] have demonstrated positive effects of the presence of a seminal coagulum upon vaginal pH (increased to 7.0) and the migration of fast linearly moving sperm into the uterus following intravaginal artificial insemination procedures. They concluded that "although still far from being compelling evidence of female cryptic choice in the spider monkey, our results acknowledge that sperm selection starts as early as the vagina, where females seemingly rely on cues provided by the seminal coagulum in favouring or opposing sperm migration."…”
Section: The Female Genitalia and Cryptic Female Choicementioning
confidence: 94%
“…For example, mouse lemurs, ring-tailed lemurs, lorises, black-handed spider monkeys, muriquis and chimpanzees all produce copulatory plugs, and all of these species have polygynandrous mating systems . Hernández-López et al [2008] have shown that, in black-handed spider monkeys (Ateles geoffroyi), the copulatory plug promotes the passage of highly motile, linearly moving sperm through the cervix. The plug also serves to buffer pH and to raise the temperature of the vagina.…”
Section: The Male Accessory Reproductive Glands and Ductsmentioning
confidence: 99%
“…Poiani [2006] suggests that the female reproductive tract and seminal fluid act as a co-evolved system; the female reproductive tract may be both enabled and inhibited by the various molecular components of seminal fluid. Hernandez-Lopez et al [2008] found that among blackhanded spider monkeys, seminal fluid effectively changes vaginal chemistry, making the female reproductive tract more hospitable for sperm and therefore fertilization. As pregnancy advances, a large amount of cervical mucus blocks off the entrance to the cervix [Hafez and Jaszczak, 1972].…”
Section: Discussionmentioning
confidence: 99%
“…Although the evolutionary and physiological mechanisms are not fully understood, copulatory plugs are thought to facilitate the reproductive success of particular males [Dixson and Anderson, 2002] and may have evolved in response to intersexual conflict [Hernandez-Lopez et al, 2008]. Previous research on copulatory plugs has traditionally focused on the facilitation of fertilization by preventing sperm leakage, slowing sperm Distribution of Macaque Copulatory Plugs 265 Folia Primatol 2009;80:264-274 release and helping sperm to reach the cervix; other hypotheses have focused on male-male competition and reproductive strategies, suggesting that copulatory plugs may serve as an obstacle for subsequent males [for a review, see Voss, 1979].…”
Section: Introductionmentioning
confidence: 99%